2014
DOI: 10.1371/journal.pcbi.1003541
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in Moving Human Groups

Abstract: How is movement of individuals coordinated as a group? This is a fundamental question of social behaviour, encompassing phenomena such as bird flocking, fish schooling, and the innumerable activities in human groups that require people to synchronise their actions. We have developed an experimental paradigm, the HoneyComb computer-based multi-client game, to empirically investigate human movement coordination and leadership. Using economic games as a model, we set monetary incentives to motivate players on a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…While we see our contribution as a first, important step to improve the data quality before modeling the flock's dynamics, it is clear that our method could be applied in other problems too. While implementation of our filter for already existing GPS data (Steiner et al., ; Gremillet et al., ; DeCesare et al., ) is an obvious application, it should be noted that our method could also be applied to position data resulting from visual methods of tracking animals (Ballerini, Cabibbo, Candelier, Cavagna, Cisbani, et al., ; Gautrais, Ginelli, Fournier, Blanco, Soria, et al., ; Bhagavatula, Claudianos, Ibbotson & Srinivasan, ; Boos, Pritz, Lange & Belz, ).…”
Section: Resultsmentioning
confidence: 99%
“…While we see our contribution as a first, important step to improve the data quality before modeling the flock's dynamics, it is clear that our method could be applied in other problems too. While implementation of our filter for already existing GPS data (Steiner et al., ; Gremillet et al., ; DeCesare et al., ) is an obvious application, it should be noted that our method could also be applied to position data resulting from visual methods of tracking animals (Ballerini, Cabibbo, Candelier, Cavagna, Cisbani, et al., ; Gautrais, Ginelli, Fournier, Blanco, Soria, et al., ; Bhagavatula, Claudianos, Ibbotson & Srinivasan, ; Boos, Pritz, Lange & Belz, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, research on birds, marine insects and fish has suggested that collective movement is influenced by non-verbal cues of velocity and the direction of movement of others [ 14 ], and knowledge of group structures based on cues from individuals [ 15 ]. Visual perception in human crowds has also been suggested to affect movements based on cues on where others in the crowd look [ 16 , 17 ] and walk [ 18 ]. A second focus has been the role of leadership and how crowds reach consensus decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the nature of leadership has been particularly fruitful within the literature of evolutionary games [8, 9, 10]. In evolutionary games, the behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Guastello [9] examined how leadership emerges in coordination-intensive groups performing evolutionary game tasks such as Stag Hunt, thus finding support for the hypothesis that leadership is a complex process where emergence can be described by means of a swallowtail catastrophe mathematical function. Furthermore, Boos et al [8] used the HoneyComb game-simulation paradigm to test how leadership and coordination emerge in human groups where participants can only rely on their visual perception to coordinate with others. The authors found that the rules of swarming behavior observed in other species like birds or bees also apply to humans (i.e., humans coordinate their movement, hence synchronizing it, by observing others and adjusting their own moving patterns), and that leadership emergence obeys to simple rules based on the visual perception of the local movement.…”
Section: Introductionmentioning
confidence: 99%